Values promotion and security management in Euro-Mediterranean relations: 'making democracy work' or 'good-enough governance'? - Fabrizio Tassinari; Ulla Holm (Danish Institute for International Studies (DIIS), 2010)
EU policy towards the Southern Mediterranean remains painfully fragmented across different lines: member states initiatives vs. EU as a whole; bilateral EU policies vs. multilateral frameworks. Underpinning these tensions, there is a continuing 'securitization' of the Mediterranean debate, which centres on threats emanating from the South, including Islamic fundamentalism, terrorism and immigration - or on challenges such as energy. On the other hand, the stated European goal in the region remains the advancement of EU norms and values - to be attained primarily through governance reforms aiming at improving the rule of law. This working paper by Fabrizio Tassinari and Ulla Holm exemplifies these discourses by focusing on the case of Italy's Mediterranean policy. In conclusion, it puts forward two competing scenarios for the future development of the Euro-Mediterranean discourse: one, based in the normative logic, termed 'making democracy work'; the other rooted in the security logic, termed 'good enough governance.'
Keywords: 330; Außenpolitik; Europäische Nachbarschaftspolitik; EU-Staaten; Italien; Mittelmeerraum